2009
DOI: 10.1021/om9002076
|View full text |Cite
|
Sign up to set email alerts
|

Facile Bifunctional Addition of Lactones and Esters at Low Temperatures. The First Intermediates in Lactone/Ester Hydrogenations

Abstract: The bifunctional addition of lactones/esters is unexpectedly facile at low temperatures. Catalytic hydrogenations of esters can be carried out under mild conditions, e.g. -20 °C under 4 atm of H 2 , but product inhibition slows these reactions oVer time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
70
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(77 citation statements)
references
References 23 publications
6
70
0
1
Order By: Relevance
“…The complex 1 also catalyzes the hydrogenation of ethyl hexanoate under 4 atm H 2 below a temperature of 0 8C, [13] and the monohydrogenation of meso-cyclic imides at 0 8C. [10] We report herein the results of our study of 1 and related compounds as catalysts for the hydrogenation of amides.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…The complex 1 also catalyzes the hydrogenation of ethyl hexanoate under 4 atm H 2 below a temperature of 0 8C, [13] and the monohydrogenation of meso-cyclic imides at 0 8C. [10] We report herein the results of our study of 1 and related compounds as catalysts for the hydrogenation of amides.…”
mentioning
confidence: 93%
“…Compound 2 a was hydrogenated with a turnover number (TON) of approximately 27 to give the ring-opened N-methanesulfonyl amino alcohol product when using 2 mol % These results are in contrast to the high activity of 1 towards the reduction of ketones, esters, and imides in THF. [10,12,13] We reasoned that catalysts such as 1 are intrinsically active towards amide hydrogenation, but they decompose [12] at the higher temperaturerequired for this transformation. We hypothesized that tethering the amine and phosphine groups would maintain activity, and prevent dissociative loss of the diamine at high temperatures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15) [61]. Since then, a few groups reported that some combined bifunctional catalysts based on the metal-NH cooperating effect, RuCl 2 (P-N) 2 , PNNP-tetradentate Ru catalyst with a base [62], and RuH 2 (diphosphine)(diamine) [63] promoted efficiently hydrogenation of esters in reasonably good reactivity. We have also found that our bifunctional catalyst Cp*Ru(P-N) and a large amount of base promote the hydrogenation of esters under more forcing conditions [22,56].…”
Section: Hydrogenation Of Esters and Lactonesmentioning
confidence: 99%
“…Homogeneous systems with ruthenium complexes have also been employed for this transformation. [12][13][14][15] Silicon chemistry combined with the use of organometallic complexes appears to be a good alternative. [16] Silanes and siloxanes have been employed with different metal sources such as Sb, [17] Rh, [18] Ru, [19] Mn, [20] Ti, [21,22] In, [23] Mo, [24] and Zn [25] to afford alcohols, ethers, or aldehydes.…”
Section: Introductionmentioning
confidence: 99%